Pengaruh Achievement Motivation, Locus of Control, dan Study Habits terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Dessy Rahmawati; Suciati Suciati (Universitas Cokroaminoto Palopo, 2023)
The study aims to analyze whether achievement motivation, internal locus of control, and study habits influence the learning outcomes of grade 7 students in four regions in Indonesia, namely Sumatera, Java, and Papua. Several experts and previous studies have shown that achievement motivation, locus of control, and study habits can be used as predictors and improve students’ mathematics learning outcomes. This research is a survey with a quantitative approach and was conducted at four schools in the XYZ Foundation. Data collection techniques using questionnaires distributed through Google Form link to measure students' achievement motivations, internal locus of control, and study habits on mathematics learning outcomes of 7th grade students. Data was collected from 183 respondents. Data analysis techniques used descriptive analysis and multiple linear regression with the IBM SPSS 25 application. Based on the result of the data analysis, the regression equation for students' achievement motivation, locus of control, and study habits on mathematics learning outcomes of 7th grade students is . Furthermore, based on the t-test result, achievement motivation with a t count of 3.961, internal locus of control with a t count of -2.994, and study habits with a t count of 1.424 are obtained. The conclusions are achievement motivation and internal locus of control partially have a positive influence and study habits do not affect the learning outcomes of grade 7 mathematics. Based on the value of , as much as 15.9% of independent variables are achievement motivation, internal locus of control, and study habits that simultaneously influence the mathematics learning outcomes of 7th grade students. Theoretical implications and implications of the research are discussed.